Genomic structure and functional characterization of the human ADAM10 promoter - Prinzen, Claudia; Můller, Ulrich; Endres, Kristina; Fahrenholz, Falk; Postina, Rolf (The FASEB journal, 2005)
The ADAM10 gene encodes a membrane-bound disintegrin-metalloproteinase, which, after overexpression in an Alzheimer disease (AD) mouse model, prevents amyloid pathology and improves long-term potentiation and memory. Because enhancing ADAM10 expression appears to be a reasonable approach for treatment of AD, we functionally analyzed the ADAM10 gene. Both human and mouse ADAM10 genes comprise approximately 160 kbp, are composed of 16 exons, and are evolutionarily highly conserved within 500 bp upstream of either translation initiation site. By using luciferase reporter assays, we demonstrate that nucleotides -2179 to -1 upstream of the human ADAM10 translation initiation site represent a functional TATA-less promoter. Within this region we identified and examined several single nucleotide polymorphisms, but did not detect significant differences in their appearance between AD and nondemented control subjects. By deletion analysis, site-directed mutagenesis, transcription factor overexpression and electrophoretic mobility shift assays, we identified nucleotides -508 to -300 as the core promoter and found Sp1, USF, and retinoic acid-responsive elements to modulate its activity. Finally, we identified vitamin A acid (RA) as an inducer of human ADAM10 promoter activity. This finding suggests that pharmacologic targeting of RA receptors may increase the expression of the alpha-secretase ADAM10 with beneficial effects on AD pathology.